Analisis Pengaruh On-Street Parking terhadap Kinerja Jalan di Pasar Jaya Ciracas, Jakarta Timur - Dicky Masrul; Adita Utami (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
This research contains an analysis of the traffic performance by dint of on-street parking, afterward the results are compared with the traffic performance if a scenario is made that there is no on-street parking activity. The purposes of this research are to determine the impact of on-street parking to road performance also to perceive the road level of service. The method used in this research is a quantitive method by direct field research. The results of this research are on-street parking activity around Jaya Ciracas Market affected the traffic performance with a difference in road capacity about 39,03%. The value of the road level of service when there is on-street parking activity is D, while when on-street parking is abolished, the road level of service can increase to C.